Rats use hippocampus to recognize positions of objects located in an inaccessible space - Levčík, David; Nekovářová, Tereza; Stuchlík, Aleš; Klement, Daniel (Hippocampus, 2013)
Rat hippocampus plays a crucial role in many spatial tasks, including recognition of position of objects, which can be approached and explored. Whether hippocampus is also necessary for recognizing positions of objects located in an inaccessible part of the environment remains unclear. To address this question, we conditioned rats to press a lever when an object displayed on a distant computer screen was in a particular position ("reward position") and not to press the lever when the object was in other positions ("nonreward positions"). After the rats had reached an asymptotic performance, the role of the dorsal hippocampus was assessed by blocking its activity with muscimol. The rats without functional dorsal hippocampus did not discriminate the reward position from the nonreward positions. Then the same rats were trained to discriminate light and dark conditions. The hippocampal inactivation did not disrupt the ability to discriminate these two conditions. It indicated that the inactivation itself had no major effect on the operant behavior and its control by visual stimuli. We conclude that rats use dorsal hippocampus for recognizing positions of objects located in an inaccessible part of the environment.
Keywords: Recognition, Psychology; Animals; Conditioning, Operant; antagonisté receptorů GABA-A; hipokampus; rozpoznávání (psychologie); GABA-A Receptor Antagonists; Muscimol; Rats, Long-Evans; Space Perception; chování zvířat; operantní podmiňování; muscimol; potkani Long-Evans; Male; krysa rodu Rattus; Behavior, Animal; Hippocampus; vnímání prostoru; zvířata; mužské pohlaví; diskriminace (psychologie); Discrimination, Psychological; Rats